Antibiotic synergist OM19r reverses aminoglycoside resistance in multidrug-resistant Escherichia coli - Cui, Qi; Yu, Han-Dong; Xu, Qi-Jun; Liu, Yue; Wang, Yu-Ting; Li, Peng-Hui; Kong, Ling-Cong; Zhang, Hai-Peng; Jiang, Xiu-Yun; Giuliodori, Anna Maria; Fabbretti, Attilio; He, Cheng-Guang; et al. (Frontiers in Microbiology, 2023)
The continued emergence and spread of multidrug-resistant (MDR) bacterial pathogens requires a new strategy to improve the efficacy of existing antibiotics, reverse bacterial resistance and extend the useful life of existing drugs. In this study, an antimicrobial peptide OM19r rich in proline and arginine was identified, which combined with aminoglycoside antibiotics, showed strong synergistic antibacterial activity against Escherichia coli. In particular, OM19r reversed the gentamicin-resistant of drug-resistant Escherichia coli B2 and increased the antibacterial activity of gentamicin against Escherichia coli B2 by 64 folds. OM19r entered Escherichia coli B2 through the intimal transporter SbmA, which inhibited the translation elongation process of bacterial protein synthesis. OM19r also facilitated the accumulation of intracellular reactive oxygen species. In animal models, OM19r significantly improved the efficacy of gentamicin against multidrug-resistant Escherichia coli B2. These findings provide a potential therapeutic option against multidrug-resistant Escherichia coli.